Withanolides array of Withania ashwagandha sp. novo populations from India - Mir, Bilal Ahmad; Khazir, Jabeena; Hakeem, Khalid Rehman; Kumar, Arun; Koul, Sushma (Elsevier, 2014)
Withania ashwagandha (Solanaceae) is an annual herb of immense medicinal value largely due to the presence of array of steroidal lactones called withanolides. The present study was conducted to determine chemical and morphological variability among five W. ashwagandha (WA) populations collected from different regions of India. Variation in the contents of three promising bioactive withanolide, namely withanolide A (WS-1), withanone (WS-2) and withaferin A (WS-3) and morphological characters including plant height, number of shoots, root yield, and leaf biomass per plant were investigated. A considerable degree of variation in these bioactive withanolides and morphological characters was detected among the populations. Plant height and plant biomass were the highest in plants collected from Manasa population followed by Hyderabad. Leaves were found to be the principle organ for WS-3 accumulation while roots mainly accumulate WS-1, suggesting a spatial variation of withanolides. Plants of Manasa population alone showed the presence of WS-2. Withanolide accumulation was also the highest in Manasa population, with 1.312% WS-3 in the leaves and 0.083% WS-1 in roots, suggesting that plants from Manasa (WA02) are elite with regard to the parameters investigated. Further, ontogenetic variation of bioactive withanolides was studied in WA02 at five developmental stages. Withanolide accumulation correlated positively with developmental stages and highest content of these withanolides was found at maturity in both roots and leaves indicating that plants be harvested at maturity stage for maximum economic benefit. These results would offer a suitable alternative for unwise random harvesting that leads to rapid reduction of the existing natural populations of W. ashwagandha and for use as potential pharmacological agents.